In-plane virtual permeability characterization of 3D woven fabrics using a hybrid experimental and numerical approach. (22nd March 2019) - Ali, M.A.; Umer, R.; Khan, K.A.; Cantwell, W.J.
Abstract: A robust platform in the form of a hybrid experimental-numerical framework is proposed for reinforcement characterization with minimal material consumption and labor costs. In this hybrid approach, X-ray micro computed tomography (XCT) images of a 3D orthogonal fabric at different levels of compaction were acquired through a non-destructive experimental setup. The XCT images were reconstructed to generate 3D models from which computational unit cells were extracted for numerical solutions of boundary value problem using governing equations of fluid dynamics. The flow field data from the numerical solution were used to compute the virtual preform permeability, which was found to be in very good agreement with benchmark experimental results. Geometrical measurements taken from XCT images were used to quantify variabilities within the preform architecture. A modified permeability model has been validated for the numerical permeability predictions. The flow field analysis and pressure drop in the flow direction suggest that the z-binder yarn poses a major obstruction to in-plane flow. The sizes of the inter-yarn channels, as well as the shape of the z-binder yarn, in the orthogonal fabric play a vital role in determining the overall in-plane permeability values. The inter-yarn gaps were found to be larger in the top and bottom layers relative to the middle layers, which results in a dominant flow regime in these outermost layers. The inter-yarn areal gaps in weft direction were found to be greater than in the warp direction. The results presented here highlight the versatility of the proposed hybrid characterization method over traditional experimental techniques.